Damages to residual stand in commercial thinnings - Bobik, Michal (SLU/Southern Swedish Forest Research Centre, 2008)
Recently more and more attention is paid to the quality of thinning operations and not only thinning efficiency. In order to produce a valuable final crop at the end of the rotation period injuries to the residual stand should be avoided. Thinnings of low quality may not favor the growth of the remaining trees and the timber value at final fellings may be diminished. Wounds imposed in thinning operations are most often reported to deteriorate the timber quality by the incidence of stain or wood decay. The study aimed at investigating the relationship between thinning damages and stand characteristics such as basal area after thinning, dominant height, age at breast height, spacing and tree species. Strip-road width, distance between strip roads and forwarder types were also included. The study is based on an inventory project carried out at SCA Skog AB in northern Sweden. Damage levels in relation to stand parameters were measured in 100 randomly chosen thinned stands in five forest districts. Data collection was based on circular sample plots. The average level of damaged trees was 5,8 %. Large variation in the number of damaged trees was found among all stands measured. No clear pattern with regard to respective forest districts could be seen. In regression analysis the group of stands dominated by Norway spruce or lodgepole pine were found to be positively correlated with the damage levels. Thinning during the winter period, i.e. December-March were found to be negatively correlated with the damage levels. Spacing after thinning was nearly-significant and also negatively correlated with the number of damaged trees. The analysis of damaged trees showed that trees with stem damages as the dominant damage type amounted to 55,7 % while trees with butt damages as the dominant damage type amouted to 44,3 %. Additionally, 61,1 % of the damaged trees were found within 5 m from the strip-road edge. An overview of the litterature concerning thinning damages was done in relation to the obtained results. Additionally, possible improvements towards the reduction of thinning damages were discussed.